Eco-Conscious Consumerism and Purchase Intention Towards Alternative Fuel Vehicles – An Examination - Vijayan, Gowri (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The increasing urgency to stop climate change and lower greenhouse gas pollution has made Alternate Fuel Vehicles (AFVs) a popular way to travel that is also good for the environment. A wide range of vehicles are considered AFVs, such as electric vehicles (EVs), hybrid vehicles, hydrogen fuel cell vehicles, and vehicles that run on biofuels or compressed natural gas (CNG). This kind of vehicle is made to use less fossil fuels, put out less CO2, and be a cleaner option to regular vehicles that run on petrol or diesel, However, despite the potential of AFVs, several challenges remain in promoting their widespread adoption. Additionally, in collectivistic societies like India, social norms play a major role in influencing the purchase intention of consumers. Therefore, getting inspiration from the Value-Belief-Norm Theory, this study tried to find out how eco-conscious consumers’ behavior influence their intention to purchase AFVs (personal values, attitudes, personal norms, social norms and purchase intention towards AFVs). Data was collected from 269 respondents through a structured questionnaire. The findings show that personal values, such as concern for the environment and social influences, like peer and societal expectations, play a significant role in encouraging consumers to choose AFVs.